Malaysian women and their role as the sandwiched generation - Ahmad, Nobaya; Abdullah, Haslinda (Universiti Putra Malaysia Press, 2013)
Women have been playing the role of caregiver in their families for generations. However, the traditional role of women as caregivers of the family, specifically as a mother and wife, is now being expanded to include caregiving for their elderly parents. The longer life expectancy of the older generation and delayed marriage are putting women in a situation where they are sandwiched between their role as wife and mother of growing-up children and their role as daughter on whom their parents depend in their old age. Based on a study of 150 women respondents working in the banking sector, this paper will focus on the roles of the sandwiched generation. Data were collected via purposive sampling by identifying women staff in selected banks; these women fulfilled the criteria of being married and having living parents. The paper will discuss issues encountered by these women, all whom reside in urban areas in Kuala Lumpur, who are sandwiched between their roles as mother, wife, employee and caregiver to the elderly. What are the problems they face in performing their many and often conflicting roles and what are their coping mechanisms when the roles come into conflict with one another? The main research question in this study is whether the women find the additional role of caregiver to the elderly an added burden causing added conflict beyond that caused by their already conflicting roles as mother, wife and employee. This study also seeks to identify the support systems in place or required to alleviate the problems encountered by these women.